PENGARUH ALOKASI DANA DESA TERHADAP MASYARAKAT DI MASA PANDEMI COVID 19 DI DESA LALONG KABUPATEN BANGGAI KEPULAUAN: THE EFFECT OF VILLAGE FUND ALLOCATION ON THE COMMUNITY DURING THE COVID 19 PANDEMIC IN LALONG VILLAGE, BANGGAI ISLANDS REGENCY - Samsidar Samsidar; Rosfianti M. Yadasang (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study was to find out whether the Allocation of Village Funds had a positive and significant effect on Community Welfare in the Lalong Village Community, Banggai Islands Regency. The research sample was the Lalong Village Community, Banggai Islands Regency using a purposive sampling technique with a total of 102 people. Methods of data collection using interviews and questionnaires. Data were analyzed descriptively quantitatively using frequency tables and simple linear regression. The results of data processing carried out through the SPSS version 25.0 program. From the results of the t test, it was found that the Village Fund Allocation variable (X) has a partial influence on Village Community Welfare (Y) in Lalong Village, Banggai Islands Regency. From the results of the Coeficienc test or t test, it was obtained t-count of 69.038 and t-table of 1.663. With this comparison, it means that it can be seen that t-count = 69.038 > t-table = 1.663 which means a positive and significant effect on Community Welfare (Y) in Community of Lalong Village, Banggai Islands Regency